Fabrication of hierarchically mesoporous CuO nanostructures and their role as heterogenous catalysts and sensors. Issue 49 (29th April 2016) - Din Sheikh, Mehraj Ud; Naikoo, Gowhar Ahmad; Thomas, Molly; Bano, Mustri; Ahirwar, Devendra; Pandit, Umar Jan; Khan, Farid
Abstract : Tween-80 templated mesoporous CuO (mpCuO) nanostructures were explored via a facile, environmentally friendly and scalable sol–gel route for heterogeneous catalysis and sensor technology. Abstract : Tween-80 templated mesoporous CuO (mpCuO) nanostructures were explored via a facile, environmentally friendly and scalable sol–gel route for heterogeneous catalysis and sensor technology. Silica nanoparticles (Si-NPs) were used as structural directing agents (SDAs) for the shape selective morphological changes of porous materials which resulted in the fabrication of nanoflowers of CuO/Si-NPs along with a great change in surface area. The mpCuO nanostructures were well characterized by FTIR, TGA, PXRD, FESEM-EDX, TEM, BET techniques. Interestingly, the as-synthesized mpCuO nanostructures showed excellent catalytic activity against the direct hydrogenation of acetone to isopropanol in the presence of sodium borohydride (NaBH4 ). In addition, mpCuO nanostructures have proved to be excellent sensor materials for simultaneous detection of some metals and biomolecules.